Analysis of Factors Associated with the Use of Long Term Contraceptive Metode - Rahmatia, Sinta Dwi; Dinengsih, Sri; Lail, Nurul Husnul (Jurnal MIDPRO, 2022)
The population problem faced by Indonesia is the high Population Growth Rate (LPP) and Total Fertility Rate (TFR). The use of MKJP is very appropriate to be applied to the condition of Indonesia which is experiencing population growth problems. The low use of MKJP in Indonesia is caused by many factors. In TPMB"S" Bogor, West Java in 2022, it was recorded from the register book that only 30% used MKJP.  This study aims to Analyze Factors Related to the Use of MKJP. This type of research is correlation analytics with Cross Sectional approaches.  The sample was 110 respondents, with random sampling. using questionnaire sheets on KB participants in TPMB "S". The results showed that respondents who had good knowledge (41.9%) using MKJP, had husband support (44.5%), despite receiving good support from health workers, had a sense of anxiety (64.6%). The test results showed that  there was a relationship of knowledge to the use of MKJP itself p-value 0.044, there was a relationship between husband support and the use of MKJP p-value 0.024, there was no relationship between health workers' support and the use of MKJP p-value 0.095. and there is a relationship between anxiety and the use of MKJP    p-value  0.014%.   There is a significant association between knowledge, spousal support, and anxiety. And there is no significant relationship between the support of health workers and the use of MKJP in TPMB "S".